Dust evolution in zoom-in cosmological simulations of galaxy formation. Issue 1 (9th February 2021) - Granato, Gian Luigi; Ragone-Figueroa, Cinthia; Taverna, Antonela; Silva, Laura; Valentini, Milena; Borgani, Stefano; Monaco, Pierluigi; Murante, Giuseppe; Tornatore, Luca
ABSTRACT: We present cosmological zoom-in hydrodynamical simulations for the formation of disc galaxies, implementing dust evolution and dust promoted cooling of hot gas. We couple an improved version of our previous treatment of dust evolution, which adopts the two-size approximation to estimate the grain-size distribution, with the MUPPI star formation and feedback subresolution model. Our dust evolution model follows carbon and silicate dust separately. To distinguish differences induced by the chaotic behaviour of simulations from those genuinely due to different simulation set-up, we run each model six times, after introducing tiny perturbations in the initial conditions. With this method, we discuss the role of various dust-related physical processes and the effect of a few possible approximations adopted in the literature. Metal depletion and dust cooling affect the evolution of the system, causing substantial variations in its stellar, gas, and dust content. We discuss possible effects on the Spectral Energy Distribution of the significant variations of the size distribution and chemical composition of grains, as predicted by our simulations during the evolution of the galaxy. We compare dust surface density, dust-to-gas ratio, and small-to-large grain mass ratio as a function of galaxy radius and gas metallicity predicted by our fiducial run with recent observational estimates for three disc galaxies of different masses. The general agreement is good, in particular taking into account that we have not adjusted our model for this purpose.